Optimizing prophylactic antibiotic regimen in patients admitted for transrectal ultrasound-guided prostate biopsies: A prospective randomized study - Ahmed Fahmy; Hazem Rhashad; Mohamed Mohi; Ahmed Elabbadie; Ahmed Kotb (Prostate International, 2016)
Background: Transrectal ultrasound-guided prostate biopsies (TRUSBx), in spite of being one of the most frequently performed urological office procedures, are associated with a spectrum of complications, most significantly including infection. The aim of the study is to evaluate the prevalence of fluoroquinolone-resistant bacteria in rectal swabs from our local population prior to TRUSBx and to identify risk factors among a patient population harboring fluoroquinolone-resistant organisms. Methods: We prospectively included 541 men who were submitted for TRUSBx in our center from March 2011 to June 2015. The indications for TRUSBx were an elevated prostate-specific antigen level and/or abnormal digital rectal exam. All patients were randomly divided into two groups: Group 1 (n = 279 cases) who received standard empirical prophylactic antibiotics and Group 2 who received targeted prophylaxis based on a rectal swab culture and susceptibility result. Differences in risk factors between quinolone-resistant and nonresistant patients were compared. Univariate and multivariate analyses were performed to identify independent potential risk factors associated with fluoroquinolone-resistant rectal flora. Results: Sixteen out of 271 men developed infectious complications after TRUSBx in the group receiving standard empirical prophylaxis (5.7%). No men in the group who received targeted prophylactic antibiotic guided by rectal swab developed infectious complications. Among the 262 patients who underwent prebiopsy rectal swab cultures, 76 men (29%) displayed fluoroquinolone-resistant rectal flora (29%). In the multivariate analysis, a history of antibiotic exposure before prostate biopsy was the only independent factor associated with an increased risk of fluoroquinolone resistance. Conclusion: Determining the prevalence of fluoroquinolone resistance in rectal flora has important implications in the selection of targeted prophylactic antibiotic regimens. Antimicrobial profiles guided by rectal swabs may prove useful to optimize prophylaxis prior to TRUSBx; this strategy is effective at reducing the rates of infectious complications, including sepsis, especially in men at higher risk of infectious complications.